A Critical Study of Malaysian Financial Conglomerates: Some Preliminary Issues - Mohd Kamal, K.A. (Universiti Malaysia Sarawak, 2011)
This paper is an introduction to my research project on Malaysian Financial conglomerates. In this paper I will discuss some issues relating to the need for a critical study of Malaysian financial conglomerates. In this paper I have briefly conceptualize and define what a financial conglomerate is in the context of Malaysia. This is done by using and adapting Granovetter’s 6 dimensions of business groups. In doing so I imagine that further research needs to be done just to identify the financial conglomerates and classify them.